Konstruksi Dan Makna Jodoushi Dantei Dalam Novel Tobu Ga Gotoku Volume 1-10 Karya Ryoutarou Shiba - Yanti Mnune, Dwika (Humanis; Volume 16. No. 3. September 2016)
The title of this study is “Construction and Meanings Jodoushi Dantei in Novel by Ryoutarou Shiba entiled Tobu ga Gotoku volume 1-10. This study aims to analyze the construction and meanings of jodoushi dantei da, no da, wake da, mono da, ~ni chigainai, hazu da, ~ni hokanaranai, and ~ni suginai in sentences of Novel by Ryoutarou entitled Tobu ga Gotoku volume 1-10. The theories used for analyzing are Verhaar (2012) and Makino&Tsutsui (1989&1995), Chaer (2007), and Sakata&Kuromachi (1993). The results of this research are jodoushi dantei constructs with adjective, X wa Y, X wa Y ga~, verb, adjective-na root of noun, noun, noun wa + noun construction, and number. Jodoushi dantei has meaning of conclusion and decision or assurance.
Keywords: jodoushi dantei, construction, meaning